(untitled) (diségno, 2018)
Last year, just a few days before Christmas, Rony Abovitz’s startup Magic Leap finally presented something concrete in regards to the mysterious, so-called ‘mixed reality,’ said to surpass both virtual reality and augmented reality. The company has been working on the project since 2011, in Florida, in great secrecy and with huge capital-risk financing by some of the major companies in the digital world, among others (more than two billion dollars have been raised to date). Basically, this revelation raised only a corner of the veil which, up to then, had hidden the invention, of which only a few bits of advance information, well-crafted to arouse curiosity and interest, had previously been disclosed.